The Effect of Boldvoice Aplication to Improve Student’s English Pronunciation Mastery at SMA Cerdas Murni - Hamidiyah, Masita; Dalimunte, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Pronunciation is an important element in language learning that students have to master. The learning of the English language is greatly impacted by advancement in technology. Numerous applications have provided more flexible and easily accessible that can be utilized via smartphones for improving pronunciation mastery. This study aims to investigate whether the use of Bold voice Application has significant effect on grade X students’ English pronunciation mastery at SMA Cerdas Murni. A quantitative approach with a pre-experimental design is the method used in this study. The population of this research is grade X SMA Cerdas Murni which consists of 130 students. The researcher used a random sampling sample, namely grade X-1 which consisted of 32 students. The instrument in this research was a pronunciation test. According to the research findings, the students' mean score was 66.53 on the pretest and 74.81 on the post-test. The t-test with a sig (2-tailed) value of 0.000 or 0.05 was used to test the hypothesis. Therefore,